Hannah Arendt and the May 1968 Events in France - LeJeune, John (HannahArendt.net, 2024)
In the essay On Violence Hannah Arendtofferedatheory of political revolutions grounded in her unique understanding of power.“Power,” Arendt argued, “corresponds to the human ability not just to act but to act in concert.” And, “Where power has disintegrated, revolutions are possible but not necessary.” At such moments, Arendt suggested, the decisive factor is the presence or absence of effective and responsible leadership. “Disintegration often becomes manifest only in direct confrontation; and even then, when power is already in the street, some group of men prepared for such an eventuality is needed to pick it up and assume responsibility.” In the same essay Arendt called the French May Days of 1968 “a textbook case of a revolutionary situation that did not develop into a revolution because there was nobody, least of all the students, prepared to seize power and the responsibility that goes with it. Nobody except, of course, de Gaulle.” This paper seeks to better understand the basis of Arendt’s assessment of the French “revolutionary situation” in 1968, and offers an Arendtian analysis of the origins, events, and outcomes of the French May Days. The central themes of this analysis are: (a) how “public happiness” was experienced, and how “power” itself was constituted on the ground by student, citizen, and labor activists, including via spontaneously organized councils;(b) what signs there were of the French body politic “disintegrating” for lack of what Arendt calls “power”; and (c) what French President Charlesde Gaulle did to “pick up power,” which the May Days protestors did not.